Internalization of the Meaning of Suffering in the Novel Hati Suhita: The Perspective of Viktor Emil Frankl’s Logotherapy - Khoiroh, Himmatul; Fadhlurachman, Muhammad Javier; Afandi, Doni (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This article discusses the internalisation of the meaning of suffering in Khilma Anis’s novel Hati Suhita using Viktor Emil Frankl’s logotherapy perspective and its application in the character development of students at Ma’had Al Jami’ah Sunan Ampel in Surabaya. This study employs a qualitative approach using literature review and content analysis of the novel’s main character. The research focuses on the forms of suffering experienced by the character Suhita, the process of discovering the meaning of life through suffering, and its relevance to the character and spiritual development of the students. The results of the study indicate that the character Suhita is able to internalise suffering as a path towards self-maturity, patience, devotion, and spirituality. Frankl’s logotherapy perspective affirms that humans can find meaning in life even in the most painful situations through the freedom to choose a meaningful attitude and life orientation. These values hold strong relevance in the development of mahasantri, particularly in building mental resilience, emotional maturity, and spirituality rooted in the pesantren tradition.